Control Architecture for Cascaded H-Bridge Inverters in Large-Scale PV Systems - Sridhar V.; Umashankar S.; Sanjeevikumar P.; Ramachandaramurthy V.K.; Mihet-Popa L.; Fedk V. (Elsevier Ltd, 2023)
Bridge circuits; Computer architecture; Distributed computer systems; Electric inverters; Level control; Photovoltaic cells; Basic building block; Cascaded H bridge (CHB); Cascaded H-bridge; Cascaded H-bridge inverters; Control architecture; Distributed processing; Multilevel; PV inverter; Controllers